Profile of renal AA amyloidosis in older and younger individuals: a single-centre experience. (3rd April 2018) - Erdogmus, Siyar; Kendi Celebi, Zeynep; Akturk, Serkan; Kumru, Gizem; Duman, Neval; Ates, Kenan; Erturk, Sehsuvar; Nergizoglu, Gokhan; Kutlay, Sim; Sengul, Sule; Keven, Kenan
Abstract: Objective: In epidemiological studies of amyloid A (AA) amyloidosis from Turkey, the most frequently cause was familial Mediterranean fever (FMF) and it occurs generally in young age population. However, there are no sufficient data regarding aetiology, clinical presentation and prognosis of renal AA amyloidosis in advanced age patients. In this study, we aimed to investigate demographic, clinical presentation, aetiology and outcomes of adults aged 60 years or older patients with biopsy-proven renal AA amyloidosis. Methods: This is a retrospective study involving 53 patients who were diagnosed with AA amyloidosis by kidney biopsy from 2006 to 2016. In all patients, kidney biopsies were performed due to asymptomatic proteinuria, nephrotic syndrome and/or renal insufficiency. The patients were separated into two groups on the basis of age (group I: ≥60 years and group II: <60 years). Outcomes of patients in terms of the requirement of renal replacement therapy and mortality were recorded. Results: In patients with group I, the causes of AA amyloidosis were as follows: FMF 16 (50%), bronchiectasis 7 (23%), chronic osteomyelitis 2 (6%), inflammatory bowel disease 2 (6%), rheumatoid arthritis 2 (6%), ankylosing spondylitis 1 (3%) and unknown aetiology 2 (6%). The underlying disorders of AA amyloidosis in group II patients were as follows: FMF 17 (81%), Behcet's disease 1 (5%) and unknown aetiology 3 (14%). No statistically significant differences were detected between two groups with regard to systolic and diastolic blood pressures, albumin, proteinuria and lipids. The combination of chronic kidney disease and nephrotic syndrome was the most common clinical presentation in group I (73%) and group II (43%) ( p  = .05). Compared to the group II, estimated glomerular filtration rate was significantly lower in group I at the time of kidney biopsy ( p  = .003). At 12-month follow-up, 61% of the group I and 33% of the group II developed end-stage kidney disease requiring dialysis, while 11% of the group I died. Conclusion: Our results indicated that renal AA amyloidosis is a rare disease in advanced age patients. At baseline and follow-up period, advanced age patients had worse kidney disease and outcomes.